Sports, Mental Health, and the Dilemmas of Fame and Success: In a Search of a Holistic Paradigm - Edin Branković (Pannoniana, 2020)
Not only is depression the most widespread disease today, but the broader issue of mental health is an open question in today’s sports world. Ensuring mental health is the key to athletes’ need too. The main aim of this research is to present a theoretical and practical approach that can possibly restore sports to where it really belongs, namely sports as a tool for the realization of bioethicity, a behavior that is in accordance with the primordial nature. This study argues that physical education, sports training, and lifestyle based and realized on a holistic paradigm have a positive effect on self-determination, mindfulness, flow experience, intrinsic motivation, and growth-mindset. The holistic paradigm implies that we should not see human beings only as a body or as a mind but a combination of both body and mind, and also as soul and spirit. A holistic approach in sports and physical exercise that includes a philosophy of sports, educational, developmental and positive psychology, neuroscience, and cultivation of “virtuous character” and “self-transformation”—as explained in Plato’s philosophy and the philosophy of nothingness of the Kyoto School respectively—can result in realization of bioethical sports.